2012
DOI: 10.2140/gt.2012.16.1639
|View full text |Cite
|
Sign up to set email alerts
|

Legendrian and transverse cables of positive torus knots

Abstract: In this paper we classify Legendrian and transverse knots in the knot types obtained from positive torus knots by cabling. This classification allows us to demonstrate several new phenomena. Specifically, we show there are knot types that have non-destabilizable Legendrian representatives whose Thurston-Bennequin invariant is arbitrarily far from maximal. We also exhibit Legendrian knots requiring arbitrarily many stabilizations before they become Legendrian isotopic. Similar new phenomena are observed for tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 14 publications
(29 reference statements)
0
54
0
Order By: Relevance
“…This continued with [31,Theorem 1.7] where it was shown that the (2, 3)cable of the (2, 3)-torus knot is not transversely simple. Techniques and results have since developed [17,55,56,58] yielding a wide range of applications and classifications results in low-dimensional contact geometry [32,34,59].…”
Section: Introductionmentioning
confidence: 99%
“…This continued with [31,Theorem 1.7] where it was shown that the (2, 3)cable of the (2, 3)-torus knot is not transversely simple. Techniques and results have since developed [17,55,56,58] yielding a wide range of applications and classifications results in low-dimensional contact geometry [32,34,59].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly the small triangles have n w´nz " 0, so we turn to the Chern class term. Referring to (12), the Euler measureχpP S q is defined bŷ…”
Section: Rationally Nullhomologous Knotsmentioning
confidence: 99%
“…It is known that (3) does not necessarily imply (2): by [ELT12], there are transverse knots representing certain cables of torus knots that have the same self-linking number but require an arbitrarily large number of stabilizations to become transversely isotopic. We do not know if (2) necessarily implies (1), although it seems unlikely.…”
Section: Some Constructions In Contact Geometrymentioning
confidence: 99%